SAT0339 The Efficacy of The 2015 Eular/acr Recommendations for The Management of Polymyalgia Rheumatica in Japanese Patients. (15th July 2016) - Ueno, A.; Yamamura, Y.; Fujita, K.; Shibutou, N.; Yamamura, M.
Abstract : Background: Glucocorticoids (GCs) are effective for polymyalgia rheumatica (PMR); however, some patients show inadequate responses to initial GC doses or relapses during GC tapering and develop side effects of GCs. The 2015 EULAR/ACR recommendations for the management of PMR has been proposed very recently, in which early introduction of methotrexate (MTX) in addition to GCs was recommended for such GC-resistance or -intolerance 1) . Similarly, we have used MTX frequently for PMR patients with relapse, prolonged GC therapy and high risk of GC adverse effects. Objectives: To examine the efficacy of this 2015 EULAR/ACR recommendation for managing Japanese patients with difficult-to-treat PMR. Methods: Thirty-five patients were diagnosed with PMR according to the 2012 EULAR/ACR provisional classification criteria for PMR 2), including 13 males and 22 females. The average (± SD) age was 69.2 ± 9.4 years; disease duration before therapy 1.9 ± 1.8 months; and the length of observation after starting treatment 23.8 ± 20.7 months. Results: All patients had active PMR, as demonstrated by high serum CRP levels (6.43 ± 4.50 mg/dL), erythrocyte sedimentation rate (ESR; 85 ± 33 mm/hr) and matrix metalloproteinase-3 (MMP-3; 188 ± 132 ng/mL). All patients with newly-diagnosed PMR were treated first with GCs (starting with the mean dose of prednisolone (PSL) of 15 mg/day; rage 10 - 60 mg/day; 60 mg/day for giant cell arteritis). Twenty-two patients experienced disease relapses, when PSL dose was reduced to 7.1 ± 3.7 mg/day at 7.9 ± 5.8 months. MTX (8.8 ± 3.4 mg/wk) was added in 21 patients and PSL was increased in a patient. Seven patients relapsed after MTX introduction, followed by adding tocilizumab (TCZ) in 6 patients and azathioprine in a patient. One patient with tocilizumab was thereafter switched to adalimumab due to insufficient response to TCZ. At present, PMR became inactive and GC was successfully withdrawn in 8 patients after total 18.0 ± 4.7 month treatment. No significant differences in basal levels of CRP, ESR and MMP-3 was found between GC-response and –resistant patients. Adverse effects included cataract (n=2), diabetes (n=1), metabolic syndrome (n=1), and osteoporosis (n=1). Conclusions: The results indicate that early addition of MTX for GC-resistance and –intolerance, as recommended by the EULAR/ACR recommendations, may be effective also for Japanese patients, but there are cases refractory to MTX addition, who will require further treatment options including TCZ. References: Dejaco C, et al. Ann Rheum Dis 2015;74:1799–807. Dasgupta B, et al. Ann Rheum Dis 2012;71:484–92. Disclosure of Interest: None declared